HUBUNGAN BEBERAPA INDIKATOR PHBS IBU RUMAH TANGGA DENGAN KEJADIAN DIARE PADA BALITA DI GAMPONG BLANG KRUENG KABUPATEN ACEH BESAR - Riski Muhammad; Burhanuddin Syam; T.M Rafsanjani (VISIKES: Jurnal Kesehatan Masyarakat, 2023)
Disease diarrhea is endemic disease in Indonesia and also a disease with potential for frequent Extraordinary Events (KLB). accompanied with death . The Clean and Healthy Behavior (PHBS) launched by the government has been running for more than 10 years, but its success is still far from expectations. This research aims to know connection a number of PHBS indicators for housewives with the risk of diarrhea in toddlers in Gampong Blang Krueng, Aceh Besar District. This research is descriptive analytic, with a case control approach. The population in this study were housewives who had toddlers who had suffered from diarrhea as many as 28 respondents and 28 respondents who did not suffer from diarrhea with a total of 56 respondents . univariate and bivariate analysis . Result _ study This shows that there is a behavioral relationship wash hand use mother 's soap House ladder with value (P-value = 0.03), (OR=3.80) , No there is a relationship between use of clean water Mother House ladder with a value (P-value = 1.00), (OR = 1.22) and there is a management relationship rubbish Mother House ladder with value (P-value = 0.01), (OR=4.50) with incident diarrhea in toddlers in G ampong B lang K rueng , A ceh Besar District . Recommended to party as _ For can increase promotion health For prevention focused diarrhea _ on implementation of PHBS in order House stairs .Keywords: Diarrhea, Handwashing, PHBS, Housewives.